Fracture Resistance Of Weakened Root Structure Reinforced With Two Types Of Composite Resin And Endodontic Sealer - Ahmad, Ahmad Mahmood (2009)
The aim of this study was to compare the fracture resistance of weakened roots obturated with a new nano HA endodontic sealer or an epoxy resin endodontic sealer and reinforced by either auto-cured or light-cured composite resin.